KAJIAN LITERATUR MODEL PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN METAKOGNITIF PADA PEMBELAJARAN KIMIA - Sukmawati; Arjuna Pramana; Firnanda Zuni Fransiska; Erlin Dwi Nurrohimi; Muhammad Ridwansyah; Agung Rahmadani (ALOTROP, 2024)
The world of education until now continues to develop but there is still a problem, namely the low learning outcomes of students. One of the factors that can cause this problem is that students do not have the ability to evaluate and regulate their cognitive processes in solving a problem in learning. Until now, teachers have tried to improve students learning outcomes through empowering metacognitive skills. The components that learners must have in learning are skills to process thinking including planning (regulation), monitoring the learning process (monitoring) and reflecting (evaluation). These components can be seen in the learning skills and learning process of learners. This literature review explores more deeply about learning models that are suitable for improving metacognitive skills in chemistry learning. The literature review uses narrative literature review type to identify learning models that can improve metacognitive skills in chemistry learning. Cooperative learning models have a great influence in improving metacognitive skills, cooperative learning models that can be used include problem-based learning, guided inquiry, problem solving, project-based learning, and self regulated learning.